Safety in agricultural machinery: an alternative in reducing production costs in Brazilian agriculture - Gomes de Moraes, Guilherme A. [UNESP]; Andreoli, Andre Luiz [UNESP]; Guarnetti dos Santos Santos, Joao Eduardo [UNESP]; Arezes, P.; Baptista, J. S.; Barroso, M. P.; Carneiro, P.; Cordeiro, P.; Costa, N.; Melo, R.; Miguel, A. S.; Perestrelo, G. (Portuguese Soc Occupational Safety & Hygiene, 2015)
It is known that the rural worker is exposed to a number of environmental factors that influence directly in the performance of his work as the mechanical vibrations and the risks of the machine tipping over. These harmful working conditions may cause occupational diseases, accidents or even death itself in the operator. Situations like these make use of financial resources in unexpected ways, for the payment of compensation in case of death or additional clearances in the event of personal injury. Also one must consider the cost in equipment that break at the time of the accident, requiring its repair or replacement. All of these factors singly or interconnected causes an increase in the cost of production. This work was based on bibliographical research and aimed to show that the use of safety devices on farm machinery can be an effective means of prevention of occupational diseases, accidents or deaths, thus promoting the reduction of production costs and the increased competitiveness of Brazilian agriculture.
Keywords: agricultural machine; job post; labor's additional; safety devices; occupational diseases